Media Framing of the ‘Barking Student’ Case in the National News of Kompas.com and Tempo.co: Framing Media atas Kasus 'Siswa Menggonggong' dalam Portal Berita Nasional Kompas.com dan Tempo.co - Zaskia Firyal Rachman; Hanna Nurhaqiqi (Academia Open, 2025)
General Background: In the digital age, online media significantly shape public perception, particularly on social issues like bullying. Specific Background: The case of a high school student coerced into barking by a parent drew national attention, highlighting divergent media narratives. Knowledge Gap: Despite growing media coverage of bullying, limited research has examined how different news platforms frame the same incident. Aims: This study investigates how Kompas.com and Tempo.co framed the "barking student" case using Robert N. Entman’s framing model. Results: Kompas.com employed an empathetic frame emphasizing child protection and psychological impact, while Tempo.co adopted a legalistic frame spotlighting law enforcement and institutional response. Novelty: By comparing two prominent Indonesian media outlets, this study reveals how contrasting journalistic orientations construct divergent social realities from a single event. Implications: The findings underscore the media’s role in agenda setting and the ethical responsibility of news platforms in shaping public discourse on sensitive issues like bullying.Highlight : The study highlights contrasting framing strategies used by Kompas.com (empathetic) and Tempo.co (legalistic) in reporting the same bullying case. It applies Robert N. Entman’s framing model, showing how different media define problems, assign causes, make moral judgments, and suggest solutions. The research underscores the power of media in shaping public perception and constructing different social realities from a single incident. Keywords : Media Framing, Bullying, Kompas.com, Tempo.co, Entman Framing Theory